Enzymatic degradation of biostatic materials based on polylactide - Richert, Agnieszka; Olewnik-Kruszkowska, Ewa (Ecological Questions, 2018)
The paper presents the research results for enzymatic degradation of biodegradable materials in proteinase K. Polylactide and its composites containing a biostatic substance in the form of sulphanilic acid salt PHMG were tested as part of the research project. Three different concentrations of the biostatic substance were used: 0.2%, 0.6% and 1.0 % of the mass. The research results of differential scanning calorimetry (DSC) for the tested materials were compared both before and after the enzymatic degradation. Photographs obtained from a scanning electron microscope (SEM) and the analysis of the foil physical mass loss confirmed that these materials were susceptible to enzymes.